Manuel D'Arriaga: O Primeiro Reitor Da Universidade De Coimbra Na República 2011
DOI: 10.14195/978-989-26-0437-4_1
|View full text |Cite
|
Sign up to set email alerts
|

Reitor da Universidade de Coimbra

Abstract: A navegação consulta e descarregamento dos títulos inseridos nas Bibliotecas Digitais UC Digitalis, UC Pombalina e UC Impactum, pressupõem a aceitação plena e sem reservas dos Termos e Condições de Uso destas Bibliotecas Digitais, disponíveis em https://digitalis.uc.pt/pt-pt/termos. Conforme exposto nos referidos Termos e Condições de Uso, o descarregamento de títulos de acesso restrito requer uma licença válida de autorização devendo o utilizador aceder ao(s) documento(s) a partir de um endereço de IP da inst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
12
0
11

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 0 publications
2
12
0
11
Order By: Relevance
“…By a least squares fit to all 366 data points, I find a shift of eight or nine 4-year periods, both with about equal likelihood. This would date the tables as made for either 1508 or 1512 in agreement with Portuguese authors on nautical history -Bensaúde, 15 De Albuquerque, 16 and Pereira da Silva 18 -who have estimated that the Munich regiment would date from around 1509.…”
Section: The Regiment Of Munichsupporting
confidence: 74%
See 1 more Smart Citation
“…By a least squares fit to all 366 data points, I find a shift of eight or nine 4-year periods, both with about equal likelihood. This would date the tables as made for either 1508 or 1512 in agreement with Portuguese authors on nautical history -Bensaúde, 15 De Albuquerque, 16 and Pereira da Silva 18 -who have estimated that the Munich regiment would date from around 1509.…”
Section: The Regiment Of Munichsupporting
confidence: 74%
“…An important difference is that Nunez's declination table is based on a maximum of 23° 30′, the same as adhered to by the school of Regiomontanus, while until then all Portuguese and Spanish tables had used Zacut's value of 23° 33′. The ecliptic longitudes that Nunez gives are systematically about 3′ lower than found via extrapolation of Zacut's tables, and Luciano Pereira da Silva 18 has hypothesized that the publication of Nunez's Tratado had met with some delay and that in reality these tables had been made for an earlier set of years.…”
Section: Pedro Nunez and The Solar Tables Of Philipp Imssermentioning
confidence: 99%
“…This same attitude as Bensaúde's one finds with Luciano Pereira da Silva, 8 Luis Mendonça de Albuquerque 4,7 and other sources quoted in these latter references. The only possibility considered is that nautical tables must have been derived by extrapolation from Zacut's tables.…”
supporting
confidence: 64%
“…This is also the conclusion of de Albuquerque in his book O Livro de Marinharia de André Pires. 4 The possibility that also declination tables would exist or have existed for 1497-1500 had earlier been suggested by Luciano Pereira da Silva, 8 who analysed the declination tables in Suma de Geographia (1519) of Martín Fernández de Enciso, 9 a Spanish geographer and explorer, and had suggested that these tables might have been prepared for Vasco da Gama's first voyage to the Indies of 1497-1499.…”
Section: Introductionmentioning
confidence: 99%
“…Essa desarmonia refreia o caminhar para a consubstanciação de decisões justas, especialmente em conflitos ambientais que, repletos de peculiaridades que o tornam complexos como é o caso de sua multicausalidade, pluralidade de atores e incertezas cientificas, necessitam de maior liberdade para a conversação entre as partes. Essa preocupação tem se tornado centro de estudos acadêmicos que intentam procurar configurações voluntárias e espontâneas, distantes da estruturação encontrada em tribunais (SILVA, 2017).…”
unclassified